Non-invasive sentinel lymph node mapping and needle guidance using clinical handheld photoacoustic imaging system in small animal - Sivasubramanian, Kathyayini (2018)
Translating photoacoustic imaging (PAI) into clinical setup is a challenge. Handheld clinical real-time PAI systems are not common. In this work, we report an integrated photoacoustic (PA) and clinical ultrasound imaging system by combining light delivery with the ultrasound probe for sentinel lymph node imaging and needle guidance in small animal. The open access clinical ultrasound platform allows seamless integration of PAI resulting in the development of handheld real-time PAI probe. Both methylene blue and indocyanine green were used for mapping the sentinel lymph node using 675 and 690 nm wavelength illuminations, respectively. Additionally, needle guidance with combined ultrasound and PAI was demonstrated using this imaging system. Up to 1.5 cm imaging depth was observed with a 10 Hz laser at an imaging frame rate of 5 frames per second, which is sufficient for future translation into human sentinel lymph node imaging and needle guidance for fine needle aspiration biopsy.